Pengembangan Aplikasi Share Our Car untuk Menambah Jumlah Okupansi Kendaraan pada Kebijakan Ganjil Genap di Daerah Khusus Ibukota Jakarta berbasis Android - Muhammad Rafsan Adhizar; Denny Sagita Rusdianto; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Share Our Car is an android-based application developed to increase the number of vehicle occupancies in the Odd-Even policy in the Special Capital Region of Jakarta. Share Our Car provides a public service forum for 4-wheeled riders who want to give rides to Jakarta residents and is also a public service forum for Jakartans who want to ride with 4-wheeled vehicle users, so that apart from being able to support government policies in the form of Odd-Even, it can also increase the number. occupancy of passengers in one vehicle so as to reduce the number of congestion that occurs in the Special Capital Region of Jakarta. This application was developed based on android so that related actors can access it easily anywhere, anytime, and can be used on an android mobile device that is connected to an internet connection and GPS and has installed the Share Our Car application. Requirements engineering is carried out as an early stage of research to find out actor identification, system requirements, and business processes. The requirements engineering stage results in 20 (twenty) functional requirements and 1 (one) non-functional requirement. These needs are used as the basis for the design and implementation stages. The system implementation is done using the Kotlin programming language. The results obtained at the testing stage using whitebox testing were 100% valid, blackbox was 100% valid, and usability using the System Usability Scale resulted in a final value of 87.5% and included in the acceptable category.